ETIKA BIROKRASI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MERAUKE - Rismawati Rismawati; Hubertus Oja (SOCIETAS, 2019)
This study aims to determine the ethics of the Population and Civil Registration Service of Merauke Regency. The population in this study were employees at the Population and Civil Registration Service of Merauke Regency, amounting to 70 people and the sample used was 40 people using the simple random sampling formula. This research uses quantitative re search. The test uses multiple linear regression analysis with variable measurements using a Likert scale and processed using the software SPSS 21 for windows. The results of this study indicate that partially understanding has a positive and significant effect on the ethics of the bureaucracy in the Population and Civil Registration Service of Merauke Regency. Partially appreciation has a positive and significant effect on the bureaucracy’s ethics in the Merauke District Population and Civil Registration Service. Partial practice has a positive and significant effect on the bureaucratic ethics of the Merauke Regency Population and Civil Registration Service. Simultaneously understanding, appreciation and practice have a positive and significant effect on the bureaucratic ethics of the Merauke Regency Population and Civil Registration Service.